Integrating Ultra-Orthodox Jewish Men in Academic Nursing Training. (November 2016) - Haron, Yafa; Azuri, Pazit
As part of the national plan for integrating the ultra-Orthodox Jewish population in academic studies and in order to promote its labor force participation, the Tel Aviv-Yaffo Academic College School for Nursing Sciences created a BSN program specifically for ultra-Orthodox men, for the first time in Israel. Ultra-Orthodox students' entry into the academic world requires the program to be culturally sensitive without compromising on quality standards. The structure and context may be ultra-Orthodox, but the contents and learning experience expose the students to a different worldview than that of their religious studies. The ultra-Orthodox way of life requires adjustments also in the area of learning aids. Most important, the students are exposed to the Internet for the first time, and some of them are even unable to use a computer. The students in the first class of male ultra-Orthodox nursing students are the pioneers of this community. Their academic success in the first stage—and integration in the labor market in the second—is a test of the national labor force integration project.